Effect of ancillary ligand on DNA and protein interaction of the two Zn (II) and Co (III) complexes: experimental and theoretical study. Issue 24 (26th December 2022) - Das, Manik; Brandao, Paola; Mati, Soumya Sundar; Roy, Saikat; Anoop, Anakuthil; James, Anjima; De, Susmita; Das, Uttam Kumar; Laha, Soumik; Mondal, Jisu; Samanta, Bidhan Chandra; Maity, Tithi
Abstract: In the present work we have developed one mononuclear Zn(II) complex [Zn(L)(H2O)] (Complex 1) by utilizing a tetracoordinated ligand H2 L, formed by simple condensation of 2, 2 dimethyl 1, 3 diamino propane and 3- ethoxy salicylaldehyde and one newly designed mononuclear Co (III) complex [Co(L)(L1)] (complex 2) by utilizing (H2 L) and 3- ethoxy salicylaldehyde(HL1) as an ancillary ligand. The newly developed complex 2 have been spectroscopically characterized. An interesting phenomenon has been noticed that in presence of ancillary ligand, the solubility in buffer solution and the thermal stability of complex 2 comparatively increases than 1 . To check the effect of ancillary ligand, present in complex 2 towards the DNA and HSA binding efficacy, both the complexes have been taken into consideration to inspect their binding potentiality with the macromolecules. The 'on', 'off' fluorescence changes in presence of DNA and HSA, the binding constant values, obtained from electronic spectral titration, iodide induced quenching, competitive binding assay, circular dichroism (CD) spectral titration, time resolved fluorescence experiment unambiguously assure the better binding efficacy of complex 2 with the signal of minor groove binding mode with DNA along with no significant conformational changes of the macromolecules. The strong and spontaneous binding of complex 2 with CT-DNA is further supported by the Isothermal Titration Calorimetry (ITC) study. Furthermore TDDFT calculation of DNA with and without complex 2 significantly authorize the formation of complex 2 -DNA adduct during the association. Finally Molecular Docking study properly verifies the experimental findings and provides justified explanation behinds experimental findings. Graphical abstract: UF0001 Communicated by Ramaswamy H. Sarma